Pembekalan Keahlian Bahasa Mandarin Bisnis Bagi Fresh Graduate Untuk Berkarir di Perusahaan Internasional - Harori, M Iqbal; Rifa’i, Ahmad; Effendi, Nur; Wardiyanto, K. Bagus (Yayasan Daarul Huda Kruengmane, 2025)
The American President's policy of implementing high import tariffs for countries in the world has created panic among entrepreneurs, so they have to think about how to survive the high tariffs surge. Companies must be able to devise the right strategy so that their business can survive. So, to remain resilient in the current economic and business conditions, companies have to buy raw materials from Tiongkok at relatively cheap prices, but it is difficult for Indonesian companies to collaborate, both in the form of purchasing production materials, making sales and looking for investors, plus the large number of Chinese companies that invest in Indonesia require employees who master Mandarin. This community service aims to provide Mandarin language skills for Fresh Graduates, enabling them to pursue a career in international companies, especially from Tiongkok. The method used is to provide training and mentoring. To overcome the problems faced by companies who want to open cooperation with investors and clients from Tiongkok. This skills improvement training for prospective employees is the right solution to the problems faced by job seekers and companies. The long-term target to be achieved in this activity is to make fresh graduates able to speak Mandarin and have a career in international companies.